“Political Citizenship” in the Digital Age: A Case Study the Defendants accused Under Article 112 of the Criminal Code - Rakyutidharm, Atchara (Journal of Social Sciences Naresuan University, 2021)
This research article is based on a qualitative research. Participant, non-participant observation and formal, informal interviews were used for data collecting, including information retrieved from documents and online sources relating to the 17 accused of disloyalty against the monarch due to their political expression. The study found that cyberspace is a crucial place for political refugees as well as the accused to express their citizenship. Advanced communication technology becomes a negotiation for Thai state’s absolute control over its people and those who live overseas. A blurred borderline between the virtual and the real world allows several forms of citizenship practices to take place, including practices that bargain for the meaning of citizenship. Therefore, any everyday practices can be considered as citizenship practices, irrespective of one’s legal status or his/her residence’s location. As such, “citizen” and “political participation” should be reconsidered.